Isoflavones enhance the plasma cholesterol-lowering activity of 7S protein in hypercholesterolemic hamsters. Issue 11 (25th October 2019) - Liu, Yuwei; Yang, Juan; Lei, Lin; Wang, Lijun; Wang, Xiaobo; Ma, Ka Ying; Yang, Xiaoquan; Chen, Zhen-Yu
Abstract : Effect of isoflavones and soybean 7S protein on plasma cholesterol. Abstract : Previous studies have shown that 7S protein is the active ingredient responsible for the plasma cholesterol-lowering activity of soybean. It is hypothesized that isoflavones in soybean could enhance the blood cholesterol-lowering activity of 7S protein. Forty-eight hamsters were divided into six groups and fed a non-cholesterol diet or one of the five high-cholesterol diets containing 12.1% 7S protein with 0–15.62 mg g −1 isoflavones. The results showed that addition of isoflavones in diets dose-dependently enhanced the plasma total cholesterol-lowering activity of 7S protein. Addition of isoflavones in 7S protein-based diets significantly reduced hepatic cholesterol accumulation by 12.6–26.1%, compared with the high cholesterol control diet. Isoflavones could also facilitate excretion of neutral sterols in a dose-dependent manner. Supplementation of isoflavones in diets favourably modulated mRNA expression and the protein mass of HMG-CoA reductase. It was concluded that the enhancing effect of isoflavones on the blood cholesterol-lowering activity of 7S protein was mediated by inhibiting the cholesterol absorption and de novo cholesterol synthesis in hypercholesterolemic hamsters.